Strategi Guru BK dalam Mereduksi Tingkat Stres Siswa Pasca Bullying di Madrasah Aliyah Negeri Palopo - Ifa Yunita; Arman Bin Anuar; Andi Nurhayati; Ainul Fahmi; Muhammad Irham Zainuri (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to find out the innovative strategies developed by Guidance and Counseling (BK) teachers at MAN Palopo in reducing the level of psychological stress in students who are victims of bullying. This research was carried out using a qualitative descriptive method where to obtain accurate information, the researchers conducted direct research to BK teachers at MAN Palopo by conducting interviews, observations, and documentation. The object of the study was carried out at MAN Palopo and the subject was a BK teacher where the researcher identified how or how the BK teacher in the school to overcome bullying behavior in the school. Based on the results of research at MAN Palopo, BK teachers' strategies have been proven to be real in the field in reducing students' stress levels after bullying. The approach used includes interventions tailored to each student's needs, a combination of how to deal with problems with a focus on feelings and the problem itself, and helping students to develop their inner strengths. The results of the study show that BK teachers play a role in helping students overcome post-bullying stress with an individual approach. In addition, positive developments were seen in both study subjects. For DF, the guidance counselor uses expressive therapy through dance and cognitive reframing techniques to boost self-confidence. Meanwhile, TM is motivated to utilize his hobby in sports and join a choir group as an emotional expression outlet. Positive developments in both subjects can be seen in the results of interviews with students who continue to show increased confidence and active involvement in school activitie In addition, MAN Palopo also implements a comprehensive anti-bullying program, demonstrating the school's commitment to creating a safe and supportive environment.